The Prognostic Value of MRI in Moderate and Severe Traumatic Brain Injury: A Systematic Review and Meta-Analysis. Issue 12 (December 2017) - Haghbayan, Hourmazd; Boutin, Amélie; Laflamme, Mathieu; Lauzier, François; Shemilt, Michèle; Moore, Lynne; Zarychanski, Ryan; Douville, Vincent; Fergusson, Dean; Turgeon, Alexis F.
Abstract : Objectives: Traumatic brain injury is a major cause of death and disability, yet many predictors of outcome are not precise enough to guide initial clinical decision-making. Although increasingly used in the early phase following traumatic brain injury, the prognostic utility of MRI remains uncertain. We thus undertook a systematic review and meta-analysis of studies evaluating the predictive value of acute MRI lesion patterns for discriminating clinical outcome in traumatic brain injury. Data Sources: MEDLINE, EMBASE, BIOSIS, and CENTRAL from inception to November 2015. Study Selection: Studies of adults who had MRI in the acute phase following moderate or severe traumatic brain injury. Our primary outcomes were all-cause mortality and the Glasgow Outcome Scale. Data Extraction: Two authors independently performed study selection and data extraction. We calculated pooled effect estimates with a random effects model, evaluated the risk of bias using a modified version of Quality in Prognostic Studies and determined the strength of evidence with the Grading of Recommendations, Assessment, Development, and Evaluation. Data Synthesis: We included 58 eligible studies, of which 27 ( n = 1, 652) contributed data to meta-analysis. Brainstem lesions were associated with all-cause mortality (risk ratio, 1.78; 95% CI, 1.01–3.15; I 2 = 43%) and unfavorable Glasgow Outcome Scale (risk ratio, 2.49; 95% CI, 1.72–3.58; I 2 = 81%) at greater than or equal to 6 months. Diffuse axonal injury patterns were associated with an increased risk of unfavorable Glasgow Outcome Scale (risk ratio, 2.46; 95% CI, 1.06–5.69; I 2 = 74%). MRI scores based on lesion depth demonstrated increasing risk of unfavorable neurologic outcome as more caudal structures were affected. Most studies were at high risk of methodological bias. Conclusions: MRI following traumatic brain injury yields important prognostic information, with several lesion patterns significantly associated with long-term survival and neurologic outcome. Given the high risk of bias in the current body of literature, large well-controlled studies are necessary to better quantify the prognostic role of early MRI in moderate and severe traumatic brain injury. Abstract : Supplemental Digital Content is available in the text.